"Hydroxychloroquine in patients with COVID-19: A Systematic Review and meta-analysis.". Issue 4 (July 2020) - Singh, Awadhesh Kumar; Singh, Akriti; Singh, Ritu; Misra, Anoop
Abstract: Backgrounds and aims: The role of hydroxychloroquine (HCQ) in the treatment of COVID-19 is not fully known. We studied the efficacy of HCQ compared to the control in COVID-19 subjects on - a. viral clearance measured by reverse transcriptase polymerase chain reaction (RT-PCR) and, b. death due to all cause. Methods: PubMed, Scopus, Cochrane and MedRxiv database were searched using the specific keywords up to April 30, 2020. Studies that met our objectives were assessed for the risk of bias applying various tools as indicated. Three studies each that reported the outcome of viral clearance by RT-PCR and death due to all cause, were meta-analyzed by applying inverse variance-weighted averages of logarithmic risk ratio (RR) using a random effects model. Heterogeneity and publication bias were assessed using the I 2 statistic and funnel plots, respectively. Results: Meta-analysis of 3 studies (n = 210) on viral clearance assessed by RT-PCR showed no benefit (RR, 1.05; 95% CI, 0.79 to 1.38; p = 0.74), although with a moderate heterogeneity (I 2 = 61.7%, p = 0.07). While meta-analysis of 3 studies (n = 474) showed a significant increase in death with HCQ, compared to the control (RR, 2.17; 95% 1.32 to 3.57; p = 0.002), without any heterogeneity (I 2 = 0.0%, p = 0.43). Conclusions: No benefit on viral clearance but a significant increase in mortality was observed with HCQ compared to control in patients with COVID-19. Highlights: The role of hydroxychloroquine in the treatment of COVID-19 is not fully known. While initial studies with hydroxychloroquine showed some ray of hope, recent studies that have emerged found either no benefit or a possible harm in COVID-19. This meta-analysis showed no benefit on viral clearance, although a significant increase in death was observed with hydroxychloroquine in patients with COVID-19, compared to the control.